THE ASSOCIATION BETWEEN KNOWLEDGE, ATTITUDES, AND TOXOPLASMOSIS PREVENTIVE PRACTICES AMONG FEMALE STUDENTS IN THE HEALTH EDUCATION CLUSTER - Dessy Triana; Mutia Syahida Khairani; Taufik Hidayat Djais; Lala Foresta Valetine Gunasari (Universitas Kusuma Husada Surakarta, 2026)
Background: Toxoplasmosis is an infectious disease resulting from exposure to the parasite Toxoplasma gondii. The prevalence of toxoplasmosis among women of reproductive age in Indonesia remains significant, attributed to factors such as individual behaviours, inadequate hygiene practices, and cultural traditions. Moreover, the prevalence of toxoplasmosis is elevated among populations with limited awareness of preventive measures, highlighting the importance of comprehensive education to decrease its incidence, particularly among women of reproductive age. Strengthening their comprehension, attitudes, and preventive behaviors is crucial as an initial strategy to reduce toxoplasmosis transmission. This study aimed to examine the association between knowledge, attitudes, and preventive practices regarding toxoplasmosis among female health education students at the University of Bengkulu.Methods: This study employed an observational, cross-sectional design. The research population comprised 925 individuals, from which 70 female students in the health education cluster at the University of Bengkulu were selected as study subjects through stratified random sampling. Data were gathered via questionnaires and analyzed using the Spearman rank correlation test.Results: The data indicated that 41 respondents (58.6%) demonstrated a high level of knowledge, 55 respondents (78.6%) maintained positive attitudes, and 59 respondents (84.3%) practiced effective preventive practices regarding toxoplasmosis. Statistical analysis revealed a significant association between knowledge level and preventive practices (p-value <0.001, r = 0.565), as well as between attitude and preventive practices (p-value <0.001, r = 0.705).Conclusion: A significant association exists between knowledge levels and attitudes regarding toxoplasmosis prevention practices.